E-078 Standard umbilical artery catheters used as diagnostic and neurointerventional guide catheters in the treatment of neonatal cerebrovascular malformations. (23rd July 2022) - Kappel, A; Orbach, D
Abstract : Background: High-flow intracranial arteriovenous malformations in neonates, including vein of Galen malformations (VOGMs), pial arteriovenous fistulas (AVFs) and dural sinus malformations (DSMs), often present with high-output cardiac failure requiring urgent or emergent intervention. Objective: Vascular access in neonates is limited by the small size of the femoral artery and the risk of complications, including thrombosis and limb ischemia. Although umbilical artery access has been described in neonates, previous reports detail exchange of the umbilical artery catheter for a conventional arterial sheath, which can be difficult and cumbersome. Here we aim to describe direct use of the umbilical artery catheter as the sheath and guide catheter in neonatal patients requiring endovascular treatment for life-threatening intracranial arteriovenous shunts. Methods: We describe a direct approach to cerebral angiography and neurointerventions in newborns using umbilical artery catheters that does not require catheter exchange, and that allows for repeated, relatively straightforward endovascular access in neonates across multiple interventions. Results: Seven consecutive neonates underwent endovascular neurointerventional procedures for the treatment of life threatening, high-flow arteriovenous shunts using a direct umbilical artery catheter access technique without procedural morbidity. Five of seven patients underwent more than one procedure in the neonatal period, between day 1 and day 10 of life. Conclusions: Use of the umbilical artery catheter itself as a diagnostic catheter for cerebral angiography or as a guide catheter for neurointerventions greatly facilitates endovascular interventions in newborns and is ideal for patients requiring multiple interventions in the neonatal period. This technique helps to mitigate the risk of neonatal femoral artery access and its complications, including thrombosis, dissection, spasm, stenosis and limb ischemia. Disclosures: A. Kappel: None. D. Orbach: None.